Bilateral Mesiodens in Monozygotic Twins: 3D Diagnostic and Management - Carla Vecchione Gurgel; Ana Lídia Soares Cota; Tatiana Yuriko Kobayashi; Salete Moura Bonifácio Silva; Maria Aparecida Andrade Moreira Machado; Daniela Rios; Daniela Gamba Garib; Thais Marchini Oliveira (Hindawi Limited, 2013)
Mesiodens is the most frequent type of supernumerary tooth and may occur in several forms, causing different local disorders, such as impaction of the anterior permanent teeth. High-resolution three-dimensional (3D) images have improved the diagnosis and treatment plan of patients with impacted and supernumerary teeth. The purpose of this paper was to report a case of two mesiodens in monozygotic twin boys with appropriate 3D diagnostic and treatment plan.